1994
DOI: 10.1093/oxfordjournals.annonc.a058931
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of etoposide-cisplatin vs. etoposide-carboplatin and irradiation in small-cell lung cancer

Abstract: Both treatments proved to be effective, with no differences in response and survival between the two treatment arms. The EC regimen was associated with significantly less toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
2
3

Year Published

1994
1994
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(94 citation statements)
references
References 24 publications
4
85
2
3
Order By: Relevance
“…27,28 The efficacy of carboplatin and etoposide combination therapy for untreated SCLC is indistinguishable from that of cisplatin and etoposide, with equivalent response rates and survival duration in randomized comparisons. 29,30 Oblimersen dose levels evaluated in the phase I study included 5 and 7 mg/kg/d. 25 This study defined a recommended phase II dose for the three-drug combination of oblimersen 7 mg/kg/d on days 1 through 8, carboplatin area under the concentration curve (AUC) 5 on day 6, and etoposide 80 mg/m 2 /d on days 6 through 8, on a 21-day cycle.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 The efficacy of carboplatin and etoposide combination therapy for untreated SCLC is indistinguishable from that of cisplatin and etoposide, with equivalent response rates and survival duration in randomized comparisons. 29,30 Oblimersen dose levels evaluated in the phase I study included 5 and 7 mg/kg/d. 25 This study defined a recommended phase II dose for the three-drug combination of oblimersen 7 mg/kg/d on days 1 through 8, carboplatin area under the concentration curve (AUC) 5 on day 6, and etoposide 80 mg/m 2 /d on days 6 through 8, on a 21-day cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Carboplatin is considered to be nearly equivalent to cisplatin in efficacy in SCLC while offering the advantage of outpatient administration (Green and Seal, 1990;Skarlos et al, 1994). Like paclitaxel, carboplatin has radiosensitising properties, which makes the combination of the two drugs with radiotherapy interesting .…”
mentioning
confidence: 99%
“…Comparing cisplatin-etoposide and carboplatin-etoposide in a randomized Phase III trial showed an equal response rate and survival although toxicity was different in both schedules, but acceptable. Myelotoxicity was higher with carboplatinetoposide whereas nephrotoxicity was higher with cisplatinetoposide (20). The comparison of etoposide-cisplatin with etoposide-cisplatin plus ifosfamide in a randomized study showed a statistically significant difference in TTP and median survival (p=0.039 and 0.044, respectively).…”
Section: Discussionmentioning
confidence: 95%